Rural Infrastructure in Armenia : Addressing Gap in Service Delivery - World Bank (Washington, DC, 2013)
This report provides public policy makers with the information necessary to develop a rural infrastructure strategy, it was not intended to represent a strategy per se, merely to highlight the issues that need greater consideration in the definition of a strategy. It starts with an inventory of existing rural infrastructure assets and a description of current institutional arrangements. It follows with a snapshot of local preferences and priorities for rural infrastructure development. It goes on to provide a provisional estimate of the costs of rehabilitating and maintaining a basic minimum level of infrastructure in all rural communities, and the incremental costs of enhanced levels, where economically justified. It concludes with a framework to assist in the setting of investment priorities and recommendations for the development of a rural strategy and action plan.